Níveis de estrogênio, estresse oxidativo e inflamação em mulheres com periodontite na pós-menopausa - uma revisão integrativa - Lopes, Reynaldo de Assis de Vasconcelos (2024)
Inflammation is the body's response to combat aggressive agents, but it can result in tissue destruction, as in periodontitis, where inflammation caused by bacteria in the dental biofilm leads to loss of bone and tissue support. The inflammatory process involves the production of pro-inflammatory mediators and an increase in Reactive Oxygen Species (ROS), contributing to the destruction of periodontal tissues, correlating with estrogen levels. The aim of the study is to analyze the relationship between low estrogen levels, associating it with oxidative stress and inflammation in postmenopausal women. The study described is an integrative review in which the Prisma Flowchart was used. The central question was formulated using the PICO strategy, focusing on postmenopausal women with periodontitis and comparing estrogen levels and markers of oxidative stress and inflammation. The research involved searching databases such as PubMed, Embase and Scopus, using specific keywords. Of the 1,575 articles initially found, 144 were read, resulting in the selection of 22 for full reading. After applying the inclusion and exclusion criteria, 10 studies were considered appropriate for the review. The reviewed studies on menopause, sex hormones and periodontal health revealed that postmenopausal women had worse periodontal health indices, suggesting the need for additional care. It was highlighted that estrogen deficiency is associated with worsening periodontitis in postmenopausal women. On the other hand, it was also observed that hormone therapy can improve periodontal status. However, the most important thing is still oral hygiene, which is considered a crucial factor in oral health. The study highlights that, although estrogen deficiency in menopause can worsen periodontitis, the results vary between studies, emphasizing the need for further studies.